Analysis of Ustaz Hanan Attaki's Sermon on Flexing the Morals of the Young Generation - Faiqul Umam; Mohammad Hasan (al-Afkar, Journal For Islamic Studies, 2026)
The phenomenon of flexing in the digital era is a behavior that demonstrates a wealth of achievements or lifestyle to gain social recognition, especially among the younger generation. This phenomenon not only impacts social and psychological aspects but is also related to moral and spiritual issues. This study aims to analyze Ustaz Hanan Attaki's lectures on flexing and their relevance to Islamic religious education. This study uses a qualitative approach with a library research type sourced from books, journals and Ustaz Hanan Attaki's lecture content on YouTube. The results show that flexing behavior can encourage hedonistic consumerism as well as riya’ (riya’), arrogance and tadzib (conceitedness), which are contrary to Islamic values. Ustaz Hanan Attaki's lectures are delivered with a communicative and persuasive approach so as to foster moral awareness of the younger generation in facing the culture of showing off on social media.